Marketing communication in the light of challenges brought about by virtualisation and interactivity - Mazurek-Łopacińska, Krystyna; Sobocińska, Magdalena (Economics and Business Review, 2016)
The development of marketing communication is multi-directional and its new dimensions and forms are related to new business ideas, the growing use of the Internet and the changing behaviour of media users. The article aims to show the main changes in the field of marketing communication which are expressed through the growing influence of the new media, the development and increasingly professional character of marketing communication, both at the stage of ideas and forms, as well as the organisation of communication actions by enterprises and other entities on the market. This is tied to the changing role of the consumer in the marketing communication process and their increased activity at all stages of the value management process. Amongst the directions of marketing communication development and its increasingly international and professional character – as manifested by various entities with a big potential to advance creative businesses – should be noted as well. Moreover an intertwining of marketing communication with pop culture is observable. The changes in marketing communication presented in this article imply a new set of challenges for marketing research. The article is based on a literature review and an analysis of selected results of quantitative research conducted as part of the Internet in marketing and the use of new technologies in cooperation between a firm and its clients project.